Soluble receptor for advanced glycation end-product (sRAGE)/pentosidine ratio: a potential risk factor determinant for Type 2 diabetic retinopathy - Ng, Z.X.; Chua, K.H.; Iqbal, T.; Kuppusamy, U.R. (2013)
This study aims to investigate potential diabetic retinopathy (DR) risk factors by evaluating the circulating levels of pentosidine, soluble receptor for advanced glycation end-product (sRAGE), advanced oxidation protein product (AOPP) as well as glutathione peroxidase (GPx) and superoxide dismutase (SOD) activities in DR patients. A total of 235 healthy controls, 171 type 2 diabetic without retinopathy (DNR) and 200 diabetic retinopathy (DR) patients were recruited. Plasma was extracted for the estimation of pentosidine, sRAGE, AOPP levels and GPx activity whereas peripheral blood mononuclear cells were disrupted for SOD activity measurement. DNR and DR patients showed significantly higher levels of plasma pentosidine, sRAGE and AOPP but lower GPx and SOD activities when compared to healthy controls. The sRAGE/pentosidine ratio in DR patients was significantly lower than the ratio detected in DNR patients. Proliferative DR patients had significantly higher levels of plasma pentosidine, sRAGE, AOPP and sRAGE/pentosidine ratio than non-proliferative DR patients. High HbA(1c) level, long duration of diabetes and low sRAGE/pentosidine ratio were determined as the risk factors for DR. This study suggests that sRAGE/pentosidine ratio could serve as a risk factor determinant for type 2 DR as it has a positive correlation with the severity of DR.